IMPLEMENTATION OF THE SELECTION OF APPAREL SUPPLIERS USING THE AHP (ANALYTICAL HIERARCHY PROCESS) METHOD AT PT. IWAK BANDENG BEKASI - Muhamad Hasan (LPPM STMIK Pringsewu, 2022)
This research was conducted in a company, namely, PT. Iwak Bandeng, will develop partnership relationships with apparel suppliers. The problem that often occurs is when choosing a supplier. The sample of this research is the decision-makers and the parties who are in the purchasing and warehouse departments who know the performance of suppliers. The sampling technique uses judgment sampling because the AHP method requires dependence on a group of experts according to the type of specialist involved in making decisions. This study uses the AHP method assisted by expert choice software. From the results of the assessment of the importance of the criteria in the selection of suppliers, the priority/weighting scales are as follows: priority I quality (0.419), priority II price (0.320), priority III delivery accuracy (0.112), priority IV accuracy in quantity (0.088) and priority V service has a priority scale (0.061). From the results of the assessment of the level of alternative importance in the selection of suppliers, the priority/weighting scale is as follows: priority I supplier CAB (0.481), priority II supplier EF (0.314), priority III supplier RJ (0.205).